Pelet Bakteri Probiotik untuk Biokontrol Xanthomonas oryzae pv. oryzae dan Viabilitas Benih Padi - Anak Agung Keswari Krisnandika; Eny Widajati; Wawan Hermawan; Giyanto Giyanto (Jurnal Fitopatologi Indonesia, 2016)
Probiotic bacteria collection from the rice plant tissue (i.e. endophytic 467 and endophytic 748 isolates), the rhizosphere (Ralstonia pickettii TT47) and that from the ground (actinomycetes 6) has been reported as biocontrol agents. The effect of pellet containing probiotic bacteria to suppress Xanthomonas oryzae pv. oryzae pathogen in rice seed has not been known thoroughly. This research was carried out to evaluate the effect of pellet containing probiotic bacteria in maintaining viability of rice seeds infected by X. oryzaepv. oryzae. A dual culture method was used to test the antagonistic activities between probiotic bacteria and X. oryzaepv. oryzae. Isolates R. pickettii TT47, endophytic 467 and actinomycetes 6 showed antagonistic activities against X. oryzae pv. oryzae. Among them, only endophytic 467 and actinomycetes 6 that showed compatibility. Pellet formulation (talc + CMC 1.5% + glycerol 1%) contain actinomycetes 6 singly or combination with endophytic 467 in infected Ciherang rice seed was able to suppress population X. oryzaepv. oryzae as long as 6 weeks storage. While, the highest percentage of seed germination and seedling growth rate during 6 weeks storage was obtained on pellet formulation with R. pickettii TT47, i.e. 86.67% and 17.17% etmal-1 respectively and significantly different with infected nonpelleted rice seed (62.67% and 11.02% etmal-1). In conclusion, the application of probiotic bacteria R. pickettii TT47, endophytic 467 and actinomycetes 6 in pellet formulation was effective to decrease X. oryzaepv. oryzae and maintain viability of infected rice seed in 6 weeks storage.